A comparative study of polyethylene and polyethylene/C60 nanocomposites modified with organic peroxide. Issue 1 (16th November 2012) - Wan, Dong; Xing, Haiping; Liu, Feng; Wang, Lu; Wang, Yujie; Tan, Haiying; Jiang, Zhiwei; Tang, Tao
Abstract Polyethylene (PE)/fullerene C60 nanocomposites, and PE samples for comparison in the presence of 0.1 wt % and 0.3 wt % 2, 5‐dimethyl‐2, 5(tert‐butylperoxy) hexane peroxide (DHBP) were prepared by melt mixing. FTIR characterization showed that reactive C60 could be grafted onto PE chains via a radical mechanism. As a result, the dispersion state of C60 was improved, and the chain extension reaction of PE macroradicals and final topological structures were largely influenced. Linear viscoelastic response of PE and PE/C60 nanocomposites containing the same content of peroxide showed much difference. Furthermore, the results of dynamic time sweep tests demonstrated that the addition of C60 could accelerate chain extension reaction. The presence of C60 could largely improve the thermal stability of PE due to the radical scavenging nature of C60. However, the crystallization behavior, melting behavior and mechanical properties of both PE and PE/C60 samples were mainly determined by the content of peroxide. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013